PENGARUH DOSIS ROOTONE-F DAN BAHAN STEK TERHADAP PERTUMBUHAN STEK BUGENVIL (Bougainvillea spectabilis L.) - Anam, Choirul (saintis, 2009)
This study was conducted in the Village Simongagrok, Dawarblandong Subdistrict, Mojokerto regency, at an altitude of 40 m asl, rainfall 1200 mm / year, temperature 270C, held in April-June 2007. This research use randomized block design (RBD) factorial pattern consisting of two factors: Dose-F Rootone composed four treatments namely: R1 (without Rootone-F), R2 (dose gram/10 Rootone-F 2.5 ml of water), R3 (dose gram/10 Rootone-F 5 ml of water), R4 (dose gram/10 Rootone-F 7.5 ml of water). Factor cuttings material consisted of three treatments: cutting materials to the upper (B1), the material cutting the middle (B2) and the bottom of the cuttings material (B3). According to analysis of variance showed significant interaction between treatment dose gram/10 Rootone-F 5 ml of water and treatment of the middle stem (R3B2). Average starting -90 days after planting. Thus the hypothesis that reads: With the treatment dose gram/10 Rootone-F 5 ml of water and materials stem cuttings middle section gives the best effect on the growth of plant cuttings bougainvillea (Bougainvillea spectabilis L.), which was conducted at study sites proved.